What was the March on Washington? - Krull, Kathleen; Tomkinson, Tim (New York : Grosset & Dunlap, 2013)
Text and illustrations look at the August 1963 March on Washington to demand equal rights for African-Americans.
What was the March on Washington? -- Separate and not equal -- The power of marches -- JFK -- No detail too small -- A crowd gathers and gathers -- Millions of footsteps -- The power of words -- "We shall overcome".
Includes bibliographical references (p. 104-105).
6.5.
3-6.
900
Keywords: Civil rights demonstrations -- Washington (D.C.) -- History -- 20th century -- Juvenile literature; African Americans -- Civil rights -- Juvenile literature; African Americans -- Civil rights; African Americans -- Civil rights; March on Washington for Jobs and Freedom -- (1963 -- Washington, D.C.); Civil rights demonstrations -- Washington (D.C.) -- History -- 20th century; African Americans -- Civil rights